Estimation of the autosomal contribution to total additive genetic variability of carcass traits in Japanese Black cattle. (13th April 2022) - Ogawa, Shinichiro; Matsuda, Hirokazu; Taniguchi, Yukio; Watanabe, Toshio; Sugimoto, Yoshikazu; Iwaisaki, Hiroaki
Abstract: We attempted to estimate the additive genetic variance explained by each autosome, using genotype data of 33, 657 single nucleotide polymorphism (SNP) markers in 2271 Japanese Black fattened steers. Traits were cold carcass weight, ribeye area, rib thickness, subcutaneous fat thickness, estimated yield percentage, and marbling score. Two mixed linear models were used: One is that (model 1) incorporating a genomic relationship matrix (G matrix) constructed by using all available SNPs, and another (model 2), incorporating two G matrices constructed by using the SNPs on one autosome and using those on the remaining autosomes. Genomic heritabilities estimated using model 1 were moderate to high. The sums of the proportions of the additive genetic variance explained by each autosome to the total genetic variance estimated by using model 2 were >90%. For carcass weight, the proportions explained by Bos taurus autosomes 6, 8, and 14 were higher than those explained by the remaining autosomes. In some cases, the estimated proportion was close to 0. The results obtained from model 2 could provide a novel insight into the genetic architecture, such as heritability per chromosome, of carcass traits in Japanese Black cattle, although further careful investigation would be required.